Enhancing safety in high-risk operations: A multilevel analysis of the role of mindful organising in translating safety climate into individual safety behaviours. (June 2021) - Renecle, Michelle; Curcuruto, Matteo; Gracia Lerín, Francisco Javier; Tomás Marco, Inés
Highlights: Group safety climate positively influences mindful organizing on a team level. Mindful organizing stimulates individual safety citizenship behaviours. Mindful organizing positively affects individual safety compliance. Mindful organizing negatively affects individual safety violations. Safety climate effects on safety behaviours are mediated by mindful organizing. Abstract: Mindful organising is a team level capability that allows teams in high-risk operations to anticipate when something is about to go wrong and quickly act to maintain the stability of the system. The present study aimed to add to our currently limited understanding of the team level conditions that are important for mindful organising to develop as well as broaden our understanding of the impact of mindful organising on individual safety behaviours. To do so, the authors test a multilevel mediation model using data collected from a sample of chemical workers. The model tested whether mindful organising mediates the relationship between team safety climate and individual in-role and extra-role safety behaviour. The findings showed that high levels of priority given to safety over other competing demands in a team is an important prerequisite for mindful organising to develop. The findings also showed that mindful organising leads to increased safety citizenship and compliance with safety protocol.